Conservation and Variability of Dengue Virus Proteins: Implications for Vaccine Design - Khan, Asif M.; Miotto, Olivo; Nascimento, Eduardo J. M.; Srinivasan, K. N.; Heiny, A. T.; Zhang, Guang Lan; Marques, E. T.; Tan, Tin Wee; Brusic, Vladimir; Salmon, Jerome; August, J. Thomas (PLOS Neglected Tropical Diseases, 2008)
Author Summary Dengue viruses (DENVs) circulate in nature as a population of 4 distinct types, each with multiple genotypes and variants, and represent an increasing global public health issue with no prophylactic and therapeutic formulations currently available. Viral genomes contain sites that are evolutionarily stable and therefore highly conserved, presumably because changes in these sites have deleterious effects on viral fitness and survival. The identification and characterization of the historical dynamics of these sites in DENV have relevance to several applications such as diagnosis and drug and vaccine development. In this study, we have identified sequence fragments that were conserved across the majority of available DENV sequences, analyzed their historical dynamics, and evaluated their relevance as candidate vaccine targets, using various bioinformatics-based methods and immune assay in human leukocyte antigen (HLA) transgenic mice. This approach provides a framework for large-scale and systematic analysis of other human pathogens.